CUSTOMER'S RESPONSES TOWARDS IN-VEHICLE COUPON RECOMMENDATION AN IMPLEMENTATION OF BUSINESS ANALYTICS CONCEPT - Genesis Sembiring Depari; Efin Shu; Cut Alya Fachriza; Joceline Chow; Jerica Wijaya; Ryanto Winata (SEAN Institute, 2022)
Marketers are constantly searching for innovative tactics to increase sales performance. One of the most popular methods is through offering coupons to potential customers. However, selecting the most potential customers is not an easy task. Customer selection and segmentation become urgently important for business. To tackle these problems, an application of business analytics method is introduced. Besides, 3 machine learning algorithms such as random forest, naive bayes, and decision tree were utilized in predicting the likelihood of coupon to be accepted by users. Eventually, Random forest was found as the most accurate algorithm with the highest prediction accuracy